Pengembangan Media Virsovere: Studi Respon Peserta Didik terhadap Media pada Materi Gelombang Bunyi - Bayu, Kharisma Nabila Maharani Putri; Anggaryani, Mita (Pendidikan Fisika Universitas Nurul Huda, 2025)
This study aims to develop a Virtual Reality (VR)-based learning media called VIRSOVERE for the sound wave topic and to assess students’ initial responses to the developed prototype. The ADDIE development model was used, but limited to the development stage, as the study focused on early-stage evaluation of the media’s feasibility and potential, rather than full-scale implementation. The media was developed using the MilleaLab platform and designed to deliver an immersive learning experience. Evaluation was carried out by distributing a semi-open response questionnaire to 25 eleventh-grade students via google form, focusing on aspects of visual, audio, material clarity, interactivity, and accessibility. The results showed that VIRSOVERE received highly positive responses, with an average total score of 85.12%. The highest scores were obtained in visual presentation and material clarity. These findings indicate that VIRSOVERE has strong potential to support students’ understanding of abstract physics concepts in an engaging and interactive manner